Cutting performance and wear characteristics of PVD coated and uncoated carbide tools in face milling Inconel 718 aerospace alloy - Jawaid, A.; Koksal, S.; Sharif, Safian (Elsevier, 2001)
In this paper, cutting performance and failure characteristics of two PVD TiN coated and an uncoated tungsten carbide grades with identical geometry are presented. Face-milling tests of Inconel 718 superalloy were performed to investigate the effect of cutting speed and feed rate on tools performance under wet conditions. Tools were thoroughly examined under SEM at two stages in order to reveal the failure modes and wear mechanisms. These stages were after cutting for 5 s and when the tool failed. It was noted that the coating resulted in a marginal improvement, as it was delaminated by adhering workpiece material at the beginning of the cut, impeding the performance of the tool for the rest of the experiment. A combination of progressive chipping and flank wear was the general mode of tool failure, former being dominant at high speeds and the latter at the low speed region. Results showed that uncoated tool performed better than coated tools at low cutting speeds while coated tools gave slightly better performance as the speed was raised.